2014
DOI: 10.1039/c4ee02539c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of semi-transparent perovskite films with centimeter-scale superior uniformity by the hybrid deposition method

Abstract: We report the development of instrumentation and methodology for fabricating large area semi-transparent organo-lead-halide perovskite films. In our method, the growth of perovskite films relies on the control of CH 3 NH 3 I flow and vapor pressure inside a vacuum chamber. Solar cell devices based on the prepared semi-transparent perovskite films as thin as $135 nm achieved an efficiency of 9.9% and a high open circuit voltage of 1.09 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
193
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(194 citation statements)
references
References 37 publications
(62 reference statements)
1
193
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] A power conversion efficiency (PCE) of 22.1% has been certified on single-junction perovskite solar cells (PSCs), almost comparable to that of state-of-the-art crystalline silicon solar cells. [10] Besides the pursuit of an even higher PCE by enhancing perovskite film quality, [11][12][13][14][15] optimizing the device another key factor. [24] For example, the most widely investigated methylammonium (CH 3 NH 3 + or MA) lead iodide (MAPbI 3 ) is reported to undergo a phase transition at 54-57 °C [30,31] and degrade at temperature over 85 °C, [32] suggesting its poor thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] A power conversion efficiency (PCE) of 22.1% has been certified on single-junction perovskite solar cells (PSCs), almost comparable to that of state-of-the-art crystalline silicon solar cells. [10] Besides the pursuit of an even higher PCE by enhancing perovskite film quality, [11][12][13][14][15] optimizing the device another key factor. [24] For example, the most widely investigated methylammonium (CH 3 NH 3 + or MA) lead iodide (MAPbI 3 ) is reported to undergo a phase transition at 54-57 °C [30,31] and degrade at temperature over 85 °C, [32] suggesting its poor thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the considerable efforts devoted to pursuing high efficiencies via improved crystallization of perovskite and searching for low-cost interface materials, 4,10-13 aesthetic semitransparent perovskite solar cells have been simultaneously receiving growing attention because of their specific application in transparent architectures, [14][15][16][17] such as windows, rooftops, greenhouses and other fashion elements. To achieve efficient semitransparent perovskite devices, both the anode and the cathode of the devices should be highly transparent and conductive in order to minimize the optical and resistance losses.…”
mentioning
confidence: 99%
“…To date, several studies have reported semitransparent perovskite solar cells, but most of these devices employed thin metal films (Al, Ag, Au) as top electrodes which were fabricated based on energy-intensive evaporation processes. [15][16][17] It is well known that, in addition to low-cost materials, the cost reduction of photovoltaic devices substantially depends on the ability to use high-throughput coating techniques in combination with roll-to-roll processing. 18 Despite its importance, however, less attention has been paid to the exploration of solution-processable transparent electrodes for perovskite solar cells.…”
mentioning
confidence: 99%
“…26 The stoichiometry and film thickness could be more precisely monitored by the quartz crystal microbalance (QCM), which is mounted inside the vacuum chamber. More recently, Lin et al studied the effect of organic p-type interlayers on the structure and composition of co-evaporation deposited perovskite films.…”
mentioning
confidence: 99%